Research on the Malting Properties of Domestic Wheat Varities - Vinko Krstanović; Kristina Habschied; Krešimir Dvojković; Krešimir Mastanjević (Fermentation, 2020)
This study aimed to establish the suitability of new Croatian wheat varieties for the production of pale wheat malt. Four new varieties/breeding lines from the Agricultural Institute Osijek were tested (Indira, OSK. 378/19, OSK. 346/20, and OSK. 353/20). The quality of starting wheat, the success of the micromalting process and the quality of finished malts were analyzed. The obtained results showed that the tested varieties/breeding lines meet the quality criteria for pale beer malt, and can be classified in the II malting quality group. The vast majority of quality indicators examined in this research showed values within the limits recommended for pale wheat malt. The obtained results were very good considering that these varieties are not intended for malting, nor in their selection process attention was paid to meet the brewing quality criteria. Due to the sensory characteristics of beer, the possibility of intervention during the malting process is limited, therefore when selecting wheat for malting, attention should be paid to the lowest possible content of total and soluble proteins, which can be achieved by appropriate agrotechnical measures in cultivation.